Does leadership matter in innovation and new business venturing? testing the mediating effect of absorptive capacity - Beh, L.S.; Imran, S. (2016)
This study aims to investigate whether leadership matters in promoting innovation and new business venturing. Using survey questionnaire, data is collected from the manufacturing SMEs of Pakistan. Structural equation modeling (SEM) technique is used for analysis. The results demonstrate that transformational leadership has positive influence on innovation, new business venturing and corporate entrepreneurship Absorptive capacity also has a mediating effect between transformational leadership with innovation and new business venturing.